PERAN USIA DAN DUKUNGAN KELUARGA DALAM MENENTUKAN KUALITAS HIDUP PASIEN HEMODIALISIS - Nur Octavianti, Rizky; Fatkhur, Handono; Sholehah, Baitus (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Chronic Kidney Disease (CKD) is a global health problem that significantly impacts patients’ quality of life, especially those undergoing hemodialysis therapy. Quality of life in CKD patients is influenced by various factors, including age and family support, which play important roles in adaptation to chronic illness and long-term treatment. Objective: This study aimed to analyze the relationship between patient age and family support with the quality of life of CKD patients undergoing hemodialysis. Methods: This study employed a quantitative design with a cross-sectional approach. A total of 103 respondents were selected using purposive sampling. Data were collected using family support and quality of life questionnaires and analyzed using the chi-square test. Results: The results showed a significant relationship between age and patient quality of life (p-value = 0.000; r = 0.613), as well as between family support and quality of life (p-value = 0.000; r = 0.569). Younger patients tended to have better quality of life than older patients, and strong family support played an important role in improving patients' quality of life. Conclusion: Age and family support are significantly associated with the quality of life of CKD patients undergoing hemodialysis. Therefore, family involvement in patient care should be enhanced, particularly for elderly patients, to optimize their quality of life.